A systematic evidence map of conservation knowledge in Chilean Patagonia. Issue 1 (19th November 2021) - Martínez‐Harms, María José; Armesto, Juan J.; Castilla, Juan Carlos; Astorga, Anna; Aylwin, José; Buschmann, Alejandro H.; Castro, Victoria; Daneri, Giovanni; Fernández, Miriam; Fuentes‐Castillo, Taryn; Gelcich, Stefan; González, Humberto E.; et al.
Abstract: Mechanisms that reliably and efficiently guide practitioners to find relevant evidence are urgent for conservation decision‐making in Chilean Patagonia. The objective of this study was to systematically collect, characterize, and synthesize the extensive evidence about conservation knowledge in Chilean Patagonia focusing on the impacts of global change drivers on ecosystems and human–nature relationships, identifying knowledge gaps, and providing policy recommendations. The quality of the evidence was assessed through a predefined level‐of‐evidence hierarchy scale, applied to a sample of the studies reviewed. We compiled ~1000 studies documenting that evidence focusing on terrestrial and marine ecosystems has grown exponentially. For terrestrial ecosystems, most studies have addressed climate change, habitat change, and invasive species; while for marine ecosystems, studies have focused on pollution, invasive species, and habitat change. We identified that an important gap is the study of the social dimensions of conservation, and future efforts should focus on incorporating traditional and local knowledge as this can help point the way to ecosystem conservation. The appraisal of the quality of the evidence showed that ~80% of the sample represented reliable evidence with underlying data and an experimental design. Enhanced efforts to deliver this evidence to decision‐makers in a user‐friendly format for evidence uptake in conservation policy are urgent. In this review, we provide a tool that can help practitioners to find evidence reliably to improve decision‐making for the conservation of ecosystems in Chilean Patagonia. Abstract : Mechanisms that guide practitioners to find the evidence reliably and efficiently are urgent for conservation decision making in Chilean Patagonia that has more than half of its territory remaining and protected. The evidence about conservation knowledge was systematically characterized and synthesized in Chilean Patagonia, identifying knowledge gaps and providing policy recommendations.